Solid-state characterization of lacidipine/PVP K(29/32) solid dispersion primed by solvent co-evaporation - Mukharya, Amit (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Lacidipine (LCDP) is a 1,4-dihydropyridine derivative categorized as an anti-hypertensive Ca2+ channel blocker having very low solubility, and thus very low oral bioavailability, which presents a challenge to the formulation scientists. Homogeneous distribution of poorly water-soluble drugs like LCDP in polyvinylpyrrolidone (PVP), a hydrophilic carrier, is definitely a suitable way to improve the bioavailability of such drugs. MATERIALS AND METHODS: The aim of the study was to develop a combined thermal, imaging, and spectroscopic approach, and characterize physical state, dissolution behavior, and elucidation of drug–PVP interaction in LCDP/PVP solid dispersion (SD) using differential scanning calorimetry (DSC), X-ray diffractometry (XRD), fourier transform infrared (FTIR) spectroscopy, and hot stage microscopy (HSM), which is the prerequisite for the development of a useful drug product. RESULTS: Dissolution studies of LCDP and its physical mixture with PVP showed less than 50% release even after 60 min, whereas SD of LCDP/PVP ratio of 1:10% w/w showed complete dissolution within 45 min. DSC and powder XRD proved the absence of crystallinity in LCDP/PVP SD at a ratio of 1:10% w/w. The FTIR spectroscopy indicated formation of hydrogen bond between LCDP and PVP. In the SD FTIR spectra, the –NH stretching vibrations and the –C=O stretch in esteric groups of LCDP shift to free –NH and C=O regions, indicating the rupture of intermolecular hydrogen bond in the crystalline structure of LCDP. CONCLUSION: Solid-state characterization by HSM, DSC, XRD, and FTIR studies, in comparison with corresponding physical mixtures, revealed the changes in solid state during the formation of dispersion and justified the formation of high-energy amorphous phase.